THE SYSTEMATIC REVIEW OF EFFECTIVE PERFORMANCE MANAGEMENT SYSTEMS IN ORGANIZATIONS - Mdhlalose, Dickson (Universitas Brawijaya, Indonesia, 2023)
This study aims to determine the impact of Performance Management Systems (PMS) on employee and organizational performance. The researcher utilized exploratory research in the study because the investigation tries to identify known/unknown factors and evaluate established hypotheses. Data was gathered through secondary research methods. Online research was conducted. Secondary information was collected using many online search tools and specialized journals, textbooks, articles in scientific journals, and online sources related to the topic. Establishing an efficient PMS is a difficult task for organizations. There are a variety of PMS tools that exist. The 360-feedback approach is the most suited appraisal method for executing the PMS for employees in an organization. PMS enhances employee performance employees' performance fairly since connections between performance reviews and improved productivity do not hold. Managers' engagement, senior management involvement, and performance feedback are key indicators of PMS's efficacy. The relevance of this research contributes to the current body of knowledge about performance management systems. Organizations would find this study's conclusions valuable and intriguing. Organizations will comprehend the influence of a successful PMS on employee and organizational performance and, as a result, devise effective countermeasures or capitalize on the advantages. This study will bring about novel knowledge of PMS and further provide future research leads. Because of its reliance on secondary sources, this investigation could only include published academic papers that existed when the study was done.